2003
DOI: 10.1177/000992280304200307
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Physician Attitudes and Practices Related to Pediatric Obesity

Abstract: The purpose of this study was to survey physicians regarding their attitudes and practices related to the treatment of pediatric obesity in a primary care setting. Surveys were sent to physicians who were members of the American Academy of Pediatrics and the American Academy of Family Physicians practicing in the Southern New England area (Connecticut, Massachusetts, and Rhode Island). The 14-item survey consisted of three main areas of focus: attitudes toward obesity, treatment and referral approaches, and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
152
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 30 publications
(5 reference statements)
8
152
1
Order By: Relevance
“…11,12 Nearly 80% of pediatricians report frustration with modifying children's obesity, however. 13 Patient motivation is associated with program adherence and predicts weight reduction. 14 Including brief motivational techniques such as motivational interviewing (MI) in weight control interventions increases effectiveness.…”
Section: What This Study Addsmentioning
confidence: 99%
“…11,12 Nearly 80% of pediatricians report frustration with modifying children's obesity, however. 13 Patient motivation is associated with program adherence and predicts weight reduction. 14 Including brief motivational techniques such as motivational interviewing (MI) in weight control interventions increases effectiveness.…”
Section: What This Study Addsmentioning
confidence: 99%
“…12,14 The present study found evidence of this concern and view, not only among GPs but also among practice nurses, school nurses, and health visitors. In addition, researchers have identified GPs feeling professionally unprepared to manage childhood obesity, 10,12 and perceiving their efforts as ineffective.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…9 Researchers have assessed primary care practitioners' views and experiences of treating childhood obesity. [10][11][12][13][14][15] However, to date, only two studies have employed qualitative research methods that enabled practitioners' views and experiences to be explored in detail. 14,15 In addition, the research undertaken so far in this area has been limited to assessing the views of GPs and practice nurses, and was carried out before the publication of the obesity care pathway and the NICE guidance.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been a few qualitative studies examining barriers to weight loss from the perspectives of health professionals (9)(10)(11) , parents (4,12,13) and children (13,14) . A survey of American health professionals identified lack of parental involvement, lack of patient motivation and lack of support services as key barriers to the management of childhood obesity (9) .…”
mentioning
confidence: 99%